Nature-based virtual reality intervention to manage stress in family caregivers of allogeneic hematopoietic stem cell transplant recipients: a two-phase pilot study protocol - Lee, Lena J.; Son, Elisa H.; Farmer, Nicole; Gerrard, Chantal; Tuason, Ralph Thadeus; Yang, Li; Kohn-Godbout, Julie; Stephens, Cory; Nahm, Eun-Shim; Smith, Leslie; Risch, Steve; Wallen, Gwenyth R. (Frontiers in Psychiatry, 2024)
Millions of family members and/or friends in the U.S. serve as unpaid caregivers for individuals with chronic conditions, such as cancer. Caregiving for someone undergoing an intense allogeneic hematopoietic stem cell transplant (HSCT) is particularly demanding, with accompanying physical and psychological stress. Increased stress and stress-related symptoms could make it difficult for caregivers to fulfill their roles and could negatively impact the health status and quality of life of themselves and the recipients. Virtual reality (VR) is a promising technology increasingly used for treatment and wellness in various medical settings. There is growing evidence that studies have reported the positive effects of the VR intervention in managing and reducing stress among diverse populations in various clinical scenarios; however, no published studies have focused on family caregivers of patients with cancer. The study aims to assess the feasibility and acceptability of a four-week nature-based VR intervention and to examine the effectiveness of the VR intervention on stress in HSCT caregivers. This study comprises two phases. Phase I of the study will be a single-arm pre-post design focused on assessing the feasibility and acceptability of the VR intervention. Phase II of the study will be a prospective randomized controlled group design to examine the effectiveness of the VR intervention on perceived stress. Adults (≥ 18 years) who serve as primary caregivers for a person who will undergo an allogeneic HSCT will be recruited. Fifteen participants will be enrolled for Phase I and 94 participants for Phase II (Active VR arm N=47; Sham VR arm N=47). The nature-based immersive VR program contains 360° high-definition videos of nature scenes along with nature sounds through a head-mounted display (HMD) for 20 minutes every day for four weeks. Primary outcome is perceived stress measured by the Perceived Stress Scale. Secondary/exploratory outcomes are stress-related symptoms (e.g., fatigue, sleep disturbance) and physiological biomarkers (e.g., cortisol, alpha-amylase). The importance and innovativeness of this study consist of using a first-of-its-kind, immersive VR technology to target stress and investigating the health outcomes assessed by validated objective biomarkers as well as self-report measures of the nature-based intervention in the caregiver population. Clinical trial registration ClinicalTrials.gov, identifier NCT 05909202.